2004
DOI: 10.1021/om034309d
|View full text |Cite
|
Sign up to set email alerts
|

Bis(imino)carbazolide Complexes of Rhodium:  Highly Nucleophilic Ligands Exerting a Dramatic Accelerating Effect on MeI Oxidative Addition

Abstract: Rhodium(I) complexes bearing a bis(imino)carbazolide ligand L and an additional neutral donor [LRh(C 2 H 4 ), 2; LRh(CO), 3] have been prepared via a salt metathesis reaction between NaL and the dimeric rhodium precursors [RhCl(C 2 H 4 ) 2 ] 2 and [RhCl(CO) 2 ] 2 , respectively. Complex 3 was also prepared by reaction of the free ligand with [RhCl(CO) 2 ] 2 , whereas a related reaction with [RhCl(C 2 H 4 ) 2 ] 2 afforded the dinuclear Rh I -Rh III ethyl complex 4. The X-ray crystal structure of 4 showed octahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 71 publications
4
37
0
Order By: Relevance
“…The clean second-order kinetics for disappearance of 1a-c are consistent with a bimolecular reaction with MeI, but do not provide information about subsequent product isomerisation steps. The apparent activation entropies are all large and negative, as frequently found for oxidative addition of MeI to square planar d 8 metal complexes, which is generally thought to proceed via an S N 2 mechanism [10,11,[13][14][15][16].…”
Section: Kinetics Of Oxidative Additionmentioning
confidence: 61%
See 2 more Smart Citations
“…The clean second-order kinetics for disappearance of 1a-c are consistent with a bimolecular reaction with MeI, but do not provide information about subsequent product isomerisation steps. The apparent activation entropies are all large and negative, as frequently found for oxidative addition of MeI to square planar d 8 metal complexes, which is generally thought to proceed via an S N 2 mechanism [10,11,[13][14][15][16].…”
Section: Kinetics Of Oxidative Additionmentioning
confidence: 61%
“…We recently reported that the bis(imino)carbazolide complex, 6 has very high reactivity towards MeI [16]. Its rate constant for oxidative addition is ca.…”
Section: Kinetics Of Oxidative Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…[59][60][61] [Rh(1)(CO) 2 ]SbF 6 was dissolved in a 3.2 m solution of MeI in acetonitrile, and the carbonyl region of the IR spectrum was monitored at 25°C over 900 min (Figure 7). During the course of the reaction, the ν(CO) bands of [Rh (1) [38] The IR spectra in Figure 7, which were determined in acetonitrile because of the poor solubility of the ionic 3 ], before CO migratory insertion can take place.…”
Section: Oxidative Addition Studies With Meimentioning
confidence: 99%
“…7,8 It was also shown that the rhodium bis(imino)carbazolide carbonyl complexes experienced a dramatically fast rate of MeI oxidative addition reaction. 9 The electrochemical studies of Pd analogue were also reported. 11 Bis(imino)carbazolyl moiety has been employed as a bridge linking two porphyrins to form a new type of Pacman porphyrin system.…”
Section: Introductionmentioning
confidence: 99%